FOREIGN EXPERIENCE IN INCREASING COMPETITIVENESS IN THE MARKET OF ADVERTISING SERVICES AND DIRECTIONS FOR ITS APPLICATION IN UZBEKISTAN (Marketing Journal, 2025)
This article examines the issues of enhancing competitiveness in the advertising services market, analyzing foreign best practices and exploring the possibilities of their application in Uzbekistan. The study highlights global trends such as digital transf ormation, innovative marketing strategies, and brand management. The current state of Uzbekistanʼs advertising market is analyzed, along with existing challenges, and practical recommendations are proposed to improve the industryʼs competitiveness based on international experience.
Keywords: advertising services; competitiveness; innovation; foreign experience; digital marketing; digital technologies; service quality; consumer behavior. 488